Effects of X-Ray Irradiation on Biological Parameters and Induced Sterility of Ephestia elutella: Establishing the Optimum Irradiation Dose and Stage - Zhao, Jun; Li, Shujun; Xu, Lu; Li, Chengjun; Li, Qi; Dewer, Youssef; Wu, Kongming (Frontiers in Physiology, 2022)
The sterile insect technique (SIT) is widely used for the inundative release of sterile mass-reared males to control lepidopteran pests. SIT based on X-ray irradiation is an eco-friendly alternative to chemical control. However, its use in Ephestia elutella, a stored tobacco pest currently controlled with insecticides, is poorly explored. This study aims to investigate the effects of X-ray irradiation on E. elutella to determine the optimal sterilizing dose and processing developmental stage for improving SIT application. The pupal stage was most suitable for irradiation that was more tolerant than the other insect stages including eggs, larvae, and adults. Subsequently, male pupae were irradiated with X-ray doses of 0, 50, 100, 150, 200, 250, and 300 Gy and mated with unirradiated females. Their emergence, longevity, egg number, egg hatch rate, developmental duration, survival rate, induced sterility, and male mating competitiveness were evaluated. The results suggest that a dose of 200 Gy can be applied to effectively induce sterility in male pupae, after which induced sterility and male mating competitiveness can be balanced by increasing the release ratio (sterile:normal). When the release ratio was 15:1, it was found that 71.91% of the wild population could be suppressed. The results of this study show that the SIT based on X-ray irradiation can be successfully used to manage E. elutella, improves our understanding of the biological effects of the SIT, and expands its future application to the control of other pests.